The protease cathepsin L regulates Th17 cell differentiation - Hou, Lifei (J Autoimmun, 2015)
Previously we reported that IL-17(+) T cells, primarily IL-17(+) γδ cells, are increased in mice lacking the protease inhibitor serpinB1 (serpinb1(−/−) mice). Here we show that serpinB1-deficient CD4 cells exhibit a cell-autonomous and selective deficiency in suppressing T helper 17 (Th17) cell differentiation. This suggested an opposing role for one or more protease in promoting Th17 differentiation. We found that several SerpinB1-inhibitable cysteine cathepsins are induced in Th17 cells, most prominently cathepsin L (catL); this was verified by peptidase assays, active site labeling and Western blots. Moreover, Th17 differentiation was suppressed by both broad cathepsin inhibitors and catL selective inhibitors. CatL is present in Th17 cells as single chain (SC)- and two-chain (TC)-forms. Inhibiting asparagine endopeptidase (AEP) blocked conversion of SC-catL to TC-catL and increased generation of serpinb1(−/−) Th17 cells, but not wild-type Th17 cells. These findings suggest that SC-catL is biologically active in promoting Th17 generation and is counter-regulated by serpinB1 and secondarily by AEP. Thus, in addition to regulation by cytokines and transcription factors, differentiation of CD4 cells to Th17 cells is actively regulated by a catL-serpinB1-AEP module. Targeting this protease regulatory module could be an approach to treating Th17 cell-driven autoimmune disorders.